A Descriptive Content Analysis of Anti-Smoking Messages among Indonesians on Instagram - Kodriati, Nurul; Fitriani, Isah; Kulsum, Zulva Ferdiana (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Many people turn to social media platforms to obtain information including information related to health. Understanding how the anti-smoking messages have been done is important to develop more structured and efficient Anti-smoking campaigns. Aims: This study aims to characterize current anti-smoking messages on Instagram in 2023 among Indonesians by employing descriptive content analysis. Methods: In March 2024, anti-smoking messages were searched on Instagram using several anti-smoking relevant hashtags such as #bahayamerokok #berhentimerokok and selected top posts for each hashtag. After eliminating duplicates, 210 Instagram posts were coded for the type of creator (individuals, company, education institution, community), message appeal (threat/fear, humor, social), and message form (picture, videos). Results: The main creator and message appeal were organizations/companies (48.1%), and threat/fear (60%) respectively. The main months of the posts being uploaded were during May or June, especially to celebrate World No Tobacco Day. The main form of the postings was in pictures (92.4%) compared to videos (7.6%). The number of likes was positively associated with the number of followers on the accounts (r=0.452, P<0.05) and the number of hashtags being used (r=0.256, P<0.05). Conclusion: Indonesian anti-smoking campaigns on social media should involve an Instagram account that has large followers to receive higher audience engagement. Routine anti-smoking messages throughout the year will ensure that the audience receives continuous education and information about the dangers of cigarette use.